2015
DOI: 10.1128/aem.00527-15
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of d -Lactate as an Energy Source Supports the Growth of Gluconobacter oxydans

Abstract: b D-Lactate was identified as one of the few available organic acids that supported the growth of Gluconobacter oxydans 621H in this study. Interestingly, the strain used D-lactate as an energy source but not as a carbon source, unlike other lactate-utilizing bacteria. The enzymatic basis for the growth of G. oxydans 621H on D-lactate was therefore investigated. Although two putative NAD-independent D-lactate dehydrogenases, GOX1253 and GOX2071, were capable of oxidizing D-lactate, GOX1253 was the only enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The results showed that most proteins contained a membrane‐associated sequence (Figure S1). Actually, only two soluble d ‐iLDHs, DLD3 in Saccharomyces cerevisiae and GOX2071 in Gluconobacter oxydans , have been characterized previously. Other reported soluble d ‐iLDHs have been shown to exist in the crude extracts of lactic acid bacteria (LAB) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that most proteins contained a membrane‐associated sequence (Figure S1). Actually, only two soluble d ‐iLDHs, DLD3 in Saccharomyces cerevisiae and GOX2071 in Gluconobacter oxydans , have been characterized previously. Other reported soluble d ‐iLDHs have been shown to exist in the crude extracts of lactic acid bacteria (LAB) .…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that most proteins contained am embrane-associated sequence ( Figure S1). Actually,o nly two soluble d-iLDHs, DLD3 in Saccharomyces cerevisiae [20] and GOX2071 in Gluconobactero xydans, [21] have been characterized previously.O ther reported soluble d-iLDHs have been shown to exist in the crude extractso fl actic acid bacteria (LAB). [22] Analysis of these two soluble d-iLDHs in the Pfam database indicatedthat they shared asimilar sequence feature, whichcontained only an FAD-binding domain at the Nt erminus and an FAD-oxidased omain at the Ct erminus.…”
mentioning
confidence: 99%
“…Most D-iLDHs belong to the flavin adenine dinucleotide (FAD)-binding oxidoreductase/transferase type 4 family, use FAD instead of FMN as the cofactor, and use quinones or cytochrome c as electron acceptors (7,14,15). However, there have been continual reports of novel types of both L-iLDHs and D-iLDHs in recent years (16)(17)(18)(19). The discovery of these novel enzymes further expands our knowledge of microbial lactate utilization, and detailed characterizations of the enzymes will be helpful in understanding the detailed mechanisms underlying these processes.…”
mentioning
confidence: 99%
“…The common NADH-oxidation pathway in Gluconobacter oxydans involves pyruvate oxidation to acetyl-coenzyme A (CoA), followed by: 1) CoA entry into the TCA cycle, which provides carbon and energy resources for bacterial growth; or 2) accumulated pyruvate entry into a non-energy-generating pathway, with acetate as the final product23. It was also suggested that accumulation of intracellular NADH might enhance hydrogen production by a putative membrane-bound hydrogenase in Enterobacter aerogenes 19.…”
Section: Discussionmentioning
confidence: 99%